Systems that support hearing families with deaf children: A scoping review - Julia Terry (PLOS ONE, 2023)
Over 90% of deaf children are born to hearing parents who have limited knowledge about deafness and require comprehensive support and information to support and communicate with their deaf child. However, little is known about the systems that support hearing families with deaf children. We performed a scoping review to provide an overview of current literature on the topic.